Unique mononuclear MnII complexes of an end-off compartmental Schiff base ligand: experimental and theoretical studies on their bio-relevant catalytic promiscuity. Issue 31 (19th July 2016) - Adhikary, Jaydeep; Chakraborty, Aratrika; Dasgupta, Sanchari; Chattopadhyay, Shyamal Kumar; Kruszynski, Rafał; Trzesowska-Kruszynska, Agata; Stepanović, Stepan; Gruden-Pavlović, Maja; Swart, Marcel; Das, Debasis
Abstract : Mn II Schiff base complexes have been experimentally and theoretically studied for their catecholase and phenoxazinone synthase activity. Abstract : Three new mononuclear manganese(ii ) complexes, namely [Mn(HL)2 ]·2ClO4 (1 ), [Mn(HL)(N(CN)2 )(H2 O)2 ]·ClO4 (2 ) and [Mn(HL)(SCN)2 ] (3 ) [LH = 4- tert -butyl-2, 6-bis-[(2-pyridin-2-yl-ethylimino)-methyl]-phenol], have been synthesized and structurally characterized. An "end-off" compartmental ligand (LH) possesses two symmetrical compartments with N2 O binding sites but accommodates only one manganese atom instead of two due to the protonation of the imine nitrogen of one compartment. Although all three complexes are mononuclear, complex1 is unique as it has a 1 : 2 metal to ligand stoichiometry. The catalytic promiscuity of complexes1–3 in terms of two different bio-relevant catalytic activities namely catecholase and phenoxazinone synthase has been thoroughly investigated. EPR and cyclic voltametric studies reveal that radical formation rather than metal centered redox participation is responsible for their catecholase-like and phenoxazinone synthase-like catalytic activity. A computational approach suggests that imine bond bound radical generation rather than phenoxo radical formation is most likely responsible for the oxidizing properties of the complexes.